ChemInform Abstract: Iron‐Doped Single Walled Carbon Nanotubes as an Efficient and Reusable Heterogeneous Catalyst for the Synthesis of Organophosphorus Compounds under Solvent‐Free Conditions. Issue 42 (1st October 2013) - Sharghi, Hashem; Ebrahimpourmoghaddam, Sakineh; Doroodmand, Mohammad Mahdi
Abstract The title catalyst is successfully employed for the three component reaction of carbonyl compounds, diethyl phosphite, and amines to give α‐aminophosphonates.